2007
DOI: 10.1007/s00262-006-0276-x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation in liposomal nanoparticles enhances the immunostimulatory, adjuvant and anti-tumor activity of subcutaneously administered CpG ODN

Abstract: Immunostimulatory oligodeoxynucleotides (ODN) containing cytosine-guanine (CpG) motifs are powerful stimulators of innate as well as adaptive immune responses, exerting their activity through triggering of the Toll-like receptor 9. We have previously shown that encapsulation in liposomal nanoparticles (LN) enhances the immunostimulatory activity of CpG ODN (LN-CpG ODN) (Mui et al. in J Pharmacol Exp Ther 298:1185, 2001). In this work we investigate the effect of encapsulation on the immunopotency of subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 64 publications
1
70
0
Order By: Relevance
“…Compared with current published studies, our TRP-2-based therapeutic nanoparticle vaccine is very potent at the low doses used for antigen and adjuvant (18,39,40). Similarly, other studies have shown improved therapeutic outcomes by either conjugating the adjuvant or the antigen onto or into delivery systems, such as poly(lactideco-glycolide) particles and liposomes, but, to our knowledge, this is the first study to show enhanced co-uptake of both adjuvant and antigen by LN-resident APCs after nanoparticle conjugation (14)(15)(16)(17)(18)(19). Furthermore, it has been shown recently that encapsulating antigens or TLR agonists in nanoparticles enhanced humoral responses compared with immunization with soluble antigen or adjuvant (41,42).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Compared with current published studies, our TRP-2-based therapeutic nanoparticle vaccine is very potent at the low doses used for antigen and adjuvant (18,39,40). Similarly, other studies have shown improved therapeutic outcomes by either conjugating the adjuvant or the antigen onto or into delivery systems, such as poly(lactideco-glycolide) particles and liposomes, but, to our knowledge, this is the first study to show enhanced co-uptake of both adjuvant and antigen by LN-resident APCs after nanoparticle conjugation (14)(15)(16)(17)(18)(19). Furthermore, it has been shown recently that encapsulating antigens or TLR agonists in nanoparticles enhanced humoral responses compared with immunization with soluble antigen or adjuvant (41,42).…”
Section: Discussionmentioning
confidence: 62%
“…S5). Furthermore, efficient LN targeting by nanoparticles and conjugation of CpG onto nanoparticles allowed a very low dose of CpG (1 mg/ mouse) to be effective, while typically much higher doses of free CpG (8-100 mg) are needed for effective adjuvant function (14)(15)(16)18). Our results showed that the vaccine-induced local immune response in the tdLN translated to greater tumor reduction than the one elicited in a non-tdLN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccine delivery systems are generally composed of particles of comparable dimensions to pathogens as bacteria and viruses (e.g. liposomes, microemulsions, immunostimulatory complexes and other nano-or microparticle systems) (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%